Entre o suporte e o controle : a articulação intersetorial da rede de serviços e o papel das terapeutas ocupacionais na Prefeitura Municipal de Campinas - SP - Avelar, Mariana Rossi (2018)
The network action strategy has been characterized by being a theme widely discussed and defended on the center of social policies, which are historically organized in sections. Their actions were (and must be) rethought and reorganized nowadays, considering the ongoing growth of social demands and complexity, especially in societies where social inequality affects wealth distribution and access to basic rights. In this context, intersectional work and network are understood as a resource to fight these social questions and its consequences, as a tool to accomplish proposals of intervention with the assisted population. On this theme we attempt to investigate the strategy of intersectional articulation between services of network composing the social policies, as a social support tool, focusing on the action of occupational therapists. As a method, 13 of the 15 coordinators of the social assistance, education and health areas were interviewed and a questionnaire was applied with 17 of the 36 occupational therapists working in the municipal network. As a method, 13 of the 15 district coordinators of social assistance, education and health were interviewed and a questionnaire was applied with 17 of the 36 occupational therapists working in the municipal network. Such data have allowed the mapping and characterization of 78 networks in Campinas-SP, city is a pioneer on proposition of intersectional articulation initiatives on the fields of social policies, especially on health policies. After the mapping, a participation and observation for four months of two networks were completed, which were chosen after indication of collaborators of this study and also by matters of convenience. Finally, nine occupational therapists participated in a dynamic activity, in order to speak about their experience and role on intersectional networks. The process made possible to verify the gap between the discourse of importance of networks and the everyday practice of it, considering it is consensus that this intersectional work is a need, however possibilities of institutional changes, in the name of effectuating it, are not offered. Beyond that, the purpose of these articulations seems to be ambivalent: they aim to assure social support, but can also act as a surveillance device for subjects. Regarding occupational therapy, it is possible to assure that, considering the social reinsertion as the main goal of this profession and specifics characteristics such as availability and flexibility shown by the profession, the resource of intersectional network is very developed, nonetheless it cannot be considered as specific or exclusive.